The Detail Behind Web-Scale: Selecting and Configuring Web-Scale Discovery Tools to Meet Music Information Retrieval Needs. - Newcomer, Nara L. (My University, 2011)
Web-scale discovery tools are rapidly gaining popularity as a purported "one-stop search" for discovering library information. Music, particularly printed music and recordings, presents unique information retrieval needs. This article identifies, explores, and makes recommendations regarding key music-related aspects to consider when selecting and implementing a discovery tool, considering scope, metadata, and interface.
Keywords: Discovery Tools; Music information retrieval; Summon; Encore; Primo Central